MOTIVASI BERPRESTASI PEGAWAI DALAM PELAKSANAAN TUGAS DI DINAS PENDIDIKAN PROVINSI SUMATERA BARAT - Muhammad Rizki; Syahril Syahril (Universitas Negeri Padang, 2019)
This research is motivated the low achievement motivation of employees in the implementation of tasks in Office Education of West Sumatra Province. This study aims to obtain information about employee achievement motivation in the implementation of tasks in the West Sumatra Provincial Office viewed from aspects of responsibility, acceptance of feedback, creativity and innovation. This type of research is descriptive with the population being employees of the Education Office of West Sumatra Province, amounting to 191 people . The sampling technique was Proportional Random Sampling so that the respondents were 68 people. The research instrument is a questionnaire (questionnaire) with a Likert Scale model with five alternative answers, namely always (SL), often (SR), sometimes (KD), rare (JR), and never (TP), which has been tested for validity and reliability. Questionnaire declared invalid by rho rho Countof rho table validity test using SPSS 16.0 to test the validity perbutir and declared all valid items with a 95% confidence level and reliability of otherwise reliable with rho Countof rho table is 0.971> 0.444. The data were processed using the formula average(mean).The results showed that achievement motivation seen from the aspect of responsibility was in the high category with an average score of 3.67. For the aspect of receiving feedback, the category is quite high with an average score of 3.55. For the aspect of creativity in the high enough category with an average score of 3.56, then the innovative aspect is in the high category with an average score of 3.67. In general, achievement motivation in carrying out tasks in the West Sumatra Provincial Education Office is in the high category with an average score of 3.67. Based on this, the authors suggest that the provision of achievement motivation be increased again so that it can increase employee motivation in work.